Dust Particle Size Distributions during Spring in Yinchuan, China - Jiangfeng Shao; Jiandong Mao (Advances in Meteorology)
Dust particle size distributions in Yinchuan, China, were measured during March and April 2014, using APS-3321 sampler. The distributions were measured under different dust conditions (background, floating dust, blowing dust, and dust storm) and statistical analyses were performed. The results showed that, under different dust conditions, the instantaneous number concentrations of dust particles differed widely. For example, during blowing sand and dust storm conditions, instantaneous dust particles concentrations varied substantially, while, under floating dust conditions, concentration differences were relatively small. The average dust particles size distributions were unimodal under all dust conditions, but the average surface area and mass size distributions were all bimodal. These distributions had peaks in different locations under different dust conditions. Under different dust conditions, wind speed and humidity were very important factors for particles size distributions. With increasing wind speed and decreasing humidity, fine particles were dominant in the atmosphere and the number and mass distributions of the coarse particles were indicative of long-range transport from surrounding deserts. Different dust conditions had different influences on PM1, PM2.5, and PM10 concentrations.